2006
DOI: 10.4028/www.scientific.net/msf.512.389
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Threads on Tool in Friction Stir Welding of Aluminum Alloys

Abstract: The effect of tool threads on the weldability and mechanical properties of 5-mm thick welded aluminum plates was investigated. The simplest shape, a circular cylinder tool without threads, and an ordinary shape, the same diameter tool with threads, were used to weld 1050-H24 and 6061-T6 aluminum alloys. The tensile strength of the joints using the tool without threads was slightly higher than or almost the same as that using the tool with threads. In the friction stir welded joints of the 1050-H24 and 6061-T6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…Although a straight probe tool without threads can also produce sufficient joints, 30) in this study, a tool with a tapered probe was used in order to extend the welding tool life. The tool dimensions and shapes are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Although a straight probe tool without threads can also produce sufficient joints, 30) in this study, a tool with a tapered probe was used in order to extend the welding tool life. The tool dimensions and shapes are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…However, in the early stages, research results did not reach an agreement in the relationship between the welding conditions and the mechanical properties of the welds. [7][8][9][10][11] Lee et al [7] and Lim et al [8] reported that decreasing the welding speed and increasing the rotation rate decreased the strength and elongation of FSW 6061Al-T651 joints. However, Ren et al's study [9] indicated that the strength of the FSW 6061Al-T651 joints did not change significantly with the variation of the rotation rate.…”
Section: Introductionmentioning
confidence: 97%
“…In the past decade, many researchers [2][3][4][5][6][7][8][9][10][11] have studied this relationship. It was reported that rotation rate, advancing speed, and tool geometry exerted significant effects on the thermal values, microstructural evolution, and mechanical properties of the FSW joints.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] For example, Scialpi et al [11] reported that the best FSW 6082Al joint was produced by a shoulder with fillet and cavity. However, the investigation by Fujii et al [10] indicated that the tool shape did not affect the mechanical properties of FSW 6061Al-T651 joints significantly. However, they did not give a detailed explanation.…”
Section: Introductionmentioning
confidence: 97%